Students’ Perception and Experience of The Use Google form as An Online Assessment tool in The English Department at Mulawarman University - hudzaifah bathinu rahmat; Weningtyas Parama Iswari; Ichi Ahada (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2024)
This study explores students' perceptions and experiences of using Google Forms as an assessment tool through a mixed-method explanatory design. Quantitative data were collected from 84 students of the 2021 cohort in the English Department at Mulawarman University using a 24-item Likert-scale questionnaire, while qualitative data were obtained from interviews with two students—one with a positive and one with a neutral perception. Findings indicate that students generally view Google Forms positively due to its simplicity, accessibility across devices, and user-friendly interface. However, concerns include its aesthetic appeal, reliance on stable internet—posing challenges for students in areas with poor connectivity—and potential academic dishonesty due to the lack of supervision. Multiple-choice questions were the most preferred, though some students valued essay questions for promoting deeper understanding. Participants emphasized the importance of receiving assessment links in advance and had mixed feelings about time limits. While the immediate feedback feature was appreciated, inconsistent implementation led to calls for more detailed responses. Overall, Google Forms is seen as a flexible and accessible assessment tool, with potential improvements in design, feedback mechanisms, and technical reliability.